Nonrelated living-donor kidney transplantation: Medical and ethical aspects - (:unkn) unknown (KARGER, 1998)
Several patients with end-stage renal disease went to Bombay for renal transplantation from nonrelated living donors and then returned to Turkey for posttransplantation follow-up. The aims of this study are to evaluate the long-term results of renal transplantation from nonrelated living donors in Turkish patients with end-stage renal disease and to discuss the ethical and social aspects of nonrelated kidney donation. One hundred and twenty-seven patients (89 males, 38 females; mean age 38.1, range 17-63 years) were investigated retrospectively. None of the patients went to Bombay on our advice. All transplantations were performed between 1991 and 1995. The mean follow-up period after transplantation was 34.2 (range 1-68) months. Graft survival rates were 85, 83, and 57% after 3 months and 1 and 5 years, respectively. Patient survival rates were 94, 93, and 92% after 3 months and 1 and 5 years, respectively. Seven patients died within the first 3 months after the transplantation. Surgical problems, infections, acute rejection, ciclosporin nephrotoxicity, and hepatic problems were common complications. We conclude that medical and surgical complications occur frequently in paid kidney transplantation, but most of these complications can be prevented by adequate preoperative management, and precautionary measures should be taken to prevent commercialization of renal transplantation before the spread of emotionally related living kidney donation.
Keywords: organ trading; non-related living-donor kidneys; kidney transplantation; THIRD-WORLD COUNTRIES; RENAL-TRANSPLANTATION; UNRELATED DONORS; HUMAN ORGANS; TURKEY; COMMERCIALIZATION; PREVALENCE; RECIPIENTS; INFECTION; COMMERCE